Improving sleep health through sleep hygiene education in adults aged 50–80 years - Pfeiffer, Ashley M.; Triplett, Craig; Schaefers, Olivia (Frontiers in Sleep, 2026)
IntroductionSleep plays a critical role in maintaining physical and cognitive health in older adults, yet sleep problems are highly prevalent in this population. Conventional management strategies often rely on pharmacological interventions, which may cause adverse side effects, evidencing the need for safe, low-cost alternatives. Sleep hygiene education offers a promising approach, and this study evaluates the efficacy of a strategy combining a one-time educational video and daily automated text messages in improving sleep quality, daytime sleepiness, and overall sleep hygiene practices among older adults.MethodsParticipants completed an electronic survey that collected demographic information and included the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Sleep Hygiene Index (SHI), Perceived Stress Scale, and Numeric Pain Rating Scale. Each participant wore a Fitbit sleep tracker for 2 weeks to establish baseline data on total sleep time, time awake, time in rapid eye movement (REM)/light/deep sleep, and sleep efficiency. Participants were then randomly assigned to a control group, a video-only group, or a video-plus-text group. Sleep tracking continued for 4 additional weeks, and all assessments were repeated at the end of the study.ResultsA total of 119 participants (mean age 66.5 ± 7.2 years; 77 females) completed the study. Paired t-tests compared pre- and post-intervention scores. Both the video-only and video-plus-text groups showed significant improvements on the PSQI, ESS, and SHI compared to the control. No significant changes were found in measured objective sleep parameters.DiscussionFindings indicate that video-based sleep hygiene education, with or without supplemental text messaging, was associated with improvements in subjective sleep quality, daytime sleepiness, and sleep hygiene behaviors. However, these improvements were not reflected in objective sleep measures, highlighting a discrepancy commonly reported in sleep research.ConclusionBrief, low-cost sleep hygiene education interventions, delivered through video or a combination of video and text messaging, may improve perceived sleep quality and sleep-related behaviors in older adults.